Dasar Program Perencanaan Dan Perancangan Arsitektur (PPA) Permukiman Islami Di Surakarta - Hernandi, Tedi (2012)
With globalization and information technology may be advancing the Indonesian Muslim community to be a formidable challenge in implementing the teachings of Islam better, globalization and technology in addition to bringing progress but have a negative impact. To anticipate this now many Islamic societies who seek settlement with the Islamic concept as an attempt to raise a family and a Muslim an Islamic environment to keep the remains of Islamic morality. Nowadays many developers who developed the concept of Islamic housing, among others: Settlement Bukit Sentul Az-zikra, Muslim Housing Darussalam III Yogyakarta. Given the urgency of these developments in Surakarta is in need, in Surakarta Belem found that using the concept of Muslim settlements. So the title of this Islamic settlements in need.